Chondrosarcoma of the spine: A case report in Sarawak General Hospital - Hernany, Shamsuddin; Chan, Wai Hoong; Mohamad Zaki, Mohd Amin (2021)
Introduction: Chondrosarcoma represent a heterogenous group of tumors characterized by their ability of cartilage formation. Chondrosarcoma of spine is a rare condition with estimated incidence around 2% to 12% . Most frequently localized in thoracic spine followed by cervical and lumbar region. Discussion: We herein report a case of spinal chondrosarcoma over thoracic spine in 58 years old gentleman. He presented with progressive swelling over the back and incomplete neurological deficit for 3 months. MRI thoracic spine showed T6 to T18 posterior spinal soft tissues, neoplastic mass with lamina arches, spinous process, adjacent posterior ribs bony erosion and spinal cord compression. Core biopsy revealed Chondrosarcoma, Grade 1. Patient underwent excision of thoracic mass, posterior instrumentation and fusion T4 -T10 with removal of pedicle of T6, T7,T8. Intraoperatively, noted tumor measuring 20cm x 20cm extending from T6-T8, involving spinous process, lamina and pedicle. Laminectomy done and tumor was excised in 1 piece together with lamina and spinous process. Postoperatively, muscle power improves to 5 from L3 to S1. Patient was discharge home well with wheelchair ambulation on day 14 post operation. Conclusion: Chondrosarcoma is known to be resistance to both chemotherapy and radiotherapy. So, surgery is critically importance in managing spinal chondrosarcoma. En-block resection of chondrosarcoma with disease free margin reduce recurrence as low as 3-8%. Knowing the facts, the stability will be greatly affected due to extensive involvement to spinal column, we decided to proceed with posterior instrumentation. Surgery should aim at preserving or even improving functionality, relieving pain and controlling local tumor recurrence, promising a prolonged survival.